2017
DOI: 10.1007/s00894-017-3476-8
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical investigation on hydrogen bond interaction of diketo/keto-enol form uracil and thymine tautomers with intercalators

Abstract: The interaction of diketo and keto-enol form of thymine and uracil tautomers with acridine (Acr), phenazine (Phen), benzo[c]cinnoline (Ben), 1,10-phenanthroline (1,10-Phe), and 4,7-phenenthroline (4,7-Phe) intercalating drug molecules was studied using density functional theory at B3LYP/6-311++G** and M05-2×/6-311++G** levels of theory. From the interaction energy, it is found that keto-enol form tautomers have stronger interaction with intercalators than diketone form tautomers. On complex formation of thymin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…In computational methods, the strength of a hydrogen bonded complex is defined as the energy needed to separate the interacting molecules to an infinite distance. [5][6][7][8][9] Hydrogen bond energy can also be estimated indirectly, using its correlations with experimental and calculated geometric parameters, [10][11][12] as well as electron density properties. [13][14][15] An analysis of electron density distribution can be carried out using quantum theory of atoms in molecules (QTAIM 16 ) or experimental electron density obtained by X-ray crystallographic measurements.…”
Section: Introductionmentioning
confidence: 99%
“…In computational methods, the strength of a hydrogen bonded complex is defined as the energy needed to separate the interacting molecules to an infinite distance. [5][6][7][8][9] Hydrogen bond energy can also be estimated indirectly, using its correlations with experimental and calculated geometric parameters, [10][11][12] as well as electron density properties. [13][14][15] An analysis of electron density distribution can be carried out using quantum theory of atoms in molecules (QTAIM 16 ) or experimental electron density obtained by X-ray crystallographic measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Uracil, a unique nucleic acid base in RNA, can form hydrogen bond with adenine to participate in transcription and translation, and then maintain inheritance, immune and other life activities. Various studies have reported that uracil can bind to water, ketones and other small molecules through hydrogen bonds [11][12][13][14][15][16][17], affecting the structure and properties of uracil. Formic acid, with the least steric hindrance in fatty acids, exists in the muscles, blood and excreta of the human body.…”
Section: Introductionmentioning
confidence: 99%